1991
DOI: 10.1111/j.1469-8137.1991.tb00975.x
|View full text |Cite
|
Sign up to set email alerts
|

A light and electron microscope study of rhizoid–ascomycete associations and flagelliform axes in British hepatics with observations on the effects of the fungi on host morphology

Abstract: SUMMARYAscomycetous fungi, identified by the presence of simple septa and Woronin bodies, form a range of highly specialized associations with the unicellular rhizoids of 46 {16*2 °.Q) of the 284 species of British liverworts. The majority of these are in the two jungermannialian suborders Lepidoziineae and Cephaloziineae, Thirt\-three species (11'6 "o) also possess flagelliform axes. These extend to depths of 20-30 cnn in peaty substrata and in most species bear abundant fungus-infected rhizoids. When grown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 52 publications
0
27
2
1
Order By: Relevance
“…Williams et al (1994) concluded that the fungal structures observed in C. varians resembled those described as mycorrhizas or mycothalli. The current study indicates that the latter term is the more appropriate, because of the apparent systemic growth of the fungus and the fact that C. varians lacks flagelliform axes, which might be considered to function in an analogous way to roots (Duckett et al, 1991). In other liverwort-fungal associations the fungal partner does not grow systemically, but proliferates in particular regions, such as in the rhizoids of other members of the Cephaloziaceae or in the inner stem region of members of the Lophoziaceae, Arnelliaceae and Scapaniaceae (Read et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Williams et al (1994) concluded that the fungal structures observed in C. varians resembled those described as mycorrhizas or mycothalli. The current study indicates that the latter term is the more appropriate, because of the apparent systemic growth of the fungus and the fact that C. varians lacks flagelliform axes, which might be considered to function in an analogous way to roots (Duckett et al, 1991). In other liverwort-fungal associations the fungal partner does not grow systemically, but proliferates in particular regions, such as in the rhizoids of other members of the Cephaloziaceae or in the inner stem region of members of the Lophoziaceae, Arnelliaceae and Scapaniaceae (Read et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In other liverwort-fungal associations the fungal partner does not grow systemically, but proliferates in particular regions, such as in the rhizoids of other members of the Cephaloziaceae or in the inner stem region of members of the Lophoziaceae, Arnelliaceae and Scapaniaceae (Read et al, 2000). Fungal hyphae within tissues of British Cephaloziella species similarly appear to be restricted to rhizoid cells and are not present in the walls between the contiguous bases of colonized rhizoids (Duckett et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8), a genus closely allied to Calypogeia and Cephalozia, the hyphae both external to and within the rhizoids fluoresced with the same intensity. In Odontoschisma (Figs 10, 11) funguscontaining rhizoids are largely restricted to leafless flagelliform axes (Duckett et al, 1991). Not only did DiOC6(3) pick out individual hyphae in rhizoid tips and shafts (Fig.…”
Section: ; S •(mentioning
confidence: 99%
“…Endophytic fungal associations have also been reported in hornworts and liverworts (Duckett et al 1991;Read et al 2000;Ligrone et al 2007). Almost 400 species of bryophilous fungi have been described (Ptaszynska et al2009) but the number is very low if we consider that there probably exist 1.5 million species of fungi (Webster and Weber 2007) and each year about 1500 new species are added by scientists.…”
Section: Introductionmentioning
confidence: 99%